Evaluations of STI care in Primary Health Care Clinics in Leribe District, Lesotho. - Nthinya, Puleng (University of Limpopo (Medunsa Campus), 2011)
Introduction STIs, including easily treatable bacterial infections such as syphilis and gonorrhoea, continue to cause a huge burden of ill health in both developing and developed countries. Syndromic management is currently the best approach for the management of sexually transmitted infections in developing countries, but its successful implementation is often questionable Objectives The overall aim of this study was to assess and compare the quality of STI services in the primary health care clinics in Leribe district, Lesotho. The specific objective of the study was to assess the availability of STI drugs, clinicians’ knowledge of STI management, and the availability of STI examination equipment Methods A descriptive cross-sectional quantitative study was conducted with 23 nurse clinicians in PHC clinics in Leribe district of Lesotho. This study explored the gaps and issues around the provision of syndromic management of STIs using the DISCA tool. Results Most of the facilities have inadequate and non reliable equipment and supplies as well poor and inadequate infrastructure. There is lack of continuous training on STI management, low complete treatment to STI clients with only a few of the health centres giving complete treatment and there was also poor contact tracing of partners. Almost all clinicians cited the correct treatment for managing male urethral syndrome. Conclusion The lack of continuous training compromised STI management because nurse clinicians lacked skills to provide quality services. In general, although the principles of syndromic management are well understood by most clinicians, there are no systems in place to support the use of these guidelines
Thesis (MPH) -- University of Limpopo, 2011.
Keywords: STI; Primary health care